A love song for Ricki Wilde / Tia Williams. - Williams, Tia, 1975- (Quercus, 2025)
Ricki Wilde has many talents, but being a Wilde isn't one of them. As the impulsive, artistic daughter of a powerful Atlanta dynasty, she's the opposite of her famous socialite sisters. Where they're long-stemmed roses, she's a dandelion: an adorable bloom that's actually a weed, born to float wherever the wind blows. In her bones, Ricki knows that somewhere, a different, more exciting life awaits her. When regal nonagenarian, Ms. Della, invites her to rent the bottom floor of her Harlem brownstone, Ricki jumps at the chance for a fresh beginning. She leaves behind her family, wealth, and chaotic romantic decisions to realize her dream of opening a flower shop.